PELAKSANAAN REDISTRIBUSI TANAH PERTANIAN DALAM RANGKA MENINGKATKAN KESEJAHTERAAN PETANI DAN MEWUJUDKAN KEMANDIRIAN DI BIDANG PANGAN DI KABUPATEN GUNUNGKIDUL - , hamseng, S.H.; , Prof. Dr. Sudjito, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Most of the farmersâ life is depend on the farming sector, and the imbalance comes from it. It is because there is a gap in the landownership. There is landlordism and in the other side the farmers have no farmland. They, who have no land work, as worker, or they who only have small farmland, whoâs called âPetani Guremâ. This condition makes them be poor. They suffer from asset poverty and structural poverty. To adjust the authority and landownership, the government has spread out UU No.56/Prp/1960 about the decision of the landreform width. The redistribution of the land object of landreform is one alternative to increasing the distribution of landownership. This thesis is to know the implementation of land redistribution